Um modelo de probabilidade para o estudo do processo de adoção de inovações - Muniz, José Norberto (Revista Ceres, 2025)
The paper’s goal is to represent the individual adoption process by means of a probabilistic mathematical model. A Markov chain is applied for the case in question, and its advantages and disadvantages are examined in comparasion with broader theoretical perspectives on the adoption of innovations.